The Trouble With Big Data How Datafication Displaces Cultural Practices - Edmond, Jennifer (Bloomsbury Studies in Digital Cultures, 2022)
This book explores the challenges society faces with big data, through the lens of culture rather than social, political or economic trends, as demonstrated in the words we use, the values that underpin our interactions, the biases and assumptions that drive us.